Sosialisasi Sistem Jaminan Produk Halal di SMKN 5 Jember - Ara Nugrahayu Nalawati; Danang Kumara Hadi; Oktarina Oktarina; Alda Wata Alim Ronita; Nanda Putri Eryani (Indonesian Journal Publisher, 2023)
Indonesia is a country with the largest Muslim population in the world. This affects the culture and patterns of public consumption of halal and thayyib products. The obligation to consume halal food and thayyib in the sharia review of Muslims is written in the Al Quran and Hadith. Demand for halal products and public awareness of purchasing halal products has increased. This is supported by the Regulation of the Minister of Religion of the Republic of Indonesia No. 26 of 2019 in article 27 which states that products that enter, circulate and trade in the territory of Indonesia must be halal certified. List of products that must be halal certified, in the form of products (food, beverages, medicines, cosmetics, chemical-biological-genetically engineered products, and used goods) and services (slaughter, processing, storage, packaging, distribution, sales and presentation). SMKN 5 Jember is one of the vocational high schools in Jember which has produced processed food products such as bread. In an effort to improve product quality and quality, it is necessary to carry out a halal certification process for bread products from the Halal Product Assurance Organizing Agency (BPJPH). This is a strong reason for academics to evaluate the socialization and mentoring activities carried out for students of SMKN 5 Jember so that they can register bakery products so that they have a halal certificate. The socialization method is carried out using 2 ways, namely lectures and question and answer. The evaluation activity was carried out by giving pre-tests (tests before material explanation) and post-tests (tests after material explanations) to students to measure the effect of socialization on students knowledge of SMKN 5 Jember regarding halal products. Based on the test results it was concluded that the socialization activities carried out were able to increase the knowledge of SMKN 5 Jember students regarding the criteria for halal products. In addition, it is hoped that the existence of halal certification for bakery products at SMKN 5 Jember will become an embryo for the formation of halal food in the school area.